Ruthless tide : the heroes and villains of the Johnstown flood, America's astonishing gilded age disaster - Roker, Al, 1954- (William Morrow, an imprint of HarperCollinsPublishers, 2018)
Presents a narrative history of the 1889 Johnstown Flood to chronicle key events, the damage that rendered the flood one of America's worst disasters, and the pivotal contributions of key figures, from dam engineer John Parke to American Red Cross founder Clara Barton.